The Tragic Lives of Oedipus Complex and Electra Complex Sufferers in Eugene O’Neill’s Mourning Becomes Electra - Meldy, Sania; Junaidi, Junaidi; Syam, Essy (Elsya : Journal of English Language Studies, 2020)
This study aims to analyse the tragic lives of Oedipus and Electra Complex sufferers in Eugene O'Neill's “Mourning Becomes Electra”. The writer applies psychoanalytical theory which fits with the characters psychological condition. The writer uses a descriptive qualitative analysis as the method to analyse. This study analyses Oedipus and Electra Complexes sufferers from characters in a drama entitled Mourning Becomes Electra that leads tragedy in a family and ends the tragic death. In this analysis, the writer finds out that the psychological conditions of those Oedipus and Electra Complex sufferers contribute to their tragic lives.